Дослідження конструкції дискового пружинного загортача просапної сівалки - Артеменко, Д. Ю.; Кислун, О. А.; Онопа, В. А.; Богатирьов, Д. В.; Artemenko, D.; Kyslun, O.; Onopa, V.; Bogatyryov, D. (ЦНТУ, 2024)
В роботі представлено результати теоретичних досліджень параметрів дискового пружинного загортача просапної сівалки. В результаті проведеного аналізу по розташуванню загортачів в конструкції секції було встановлено, що ефективніше розташовувати загортачі після сошника, що дозволяє укривати насіння вологим шаром ґрунту та створювати сприятливі умови для його проростання. З метою підвищення ефективності роботи загортачів був розроблений новий дисковий загортач пружинного типу. У процесі його дослідження було визначено, що основними параметрами, які впливають на процес роботи загортача є його кут атаки, швидкість руху сівалки та дальність переміщення ґрунту в бік борозни. Отримана теоретична залежність, що показує вплив кута атаки на дальність переміщення ґрунту загортачем в залежності від фізико-механічних властивостей ґрунту. The study presents the results of theoretical research on the design and technological parameters of the spring-loaded disc covering device for row crop seeders. The analysis of existing covering devices and their technological processes revealed that they do not provide optimal sequential seed covering with moist soil layers followed by drier ones. Most designs, positioned after pressing rollers, primarily perform mulching and leveling of the furrow surface, which leads to mixing soil layers of different depths. It was determined that placing the covering devices immediately after the seed opener is more effective. This allows seeds to be covered with a moist soil layer immediately after being placed in the furrow, followed by a mulched drier layer. This approach helps retain moisture in the seed zone and creates favorable conditions for germination. To address the shortcomings of the reviewed covering devices, a new spring-loaded disc covering device was developed. This device combines a flat, single-edged disc positioned at an angle of attack to the direction of movement. A conical press is mounted on the outer edge of the disc, connected via a hub to a vertical pressure spring. The vertical pressure spring applies force to the working surface of the covering device and is positioned at an angle in the vertical plane relative to the row axis.
Research of the Design of a disc Spring Closing Device for a Row Crop Planter
Keywords: сприятливі умови; загортач; загортання насіння; дисковий пружинний загортач; підвищення врожайності просапних культур; favorable conditions; covering device; seed covering; spring-loaded disc covering device; increasing yield of row crops